The bank specific determinants of non-performing loans in Malaysia / Sofie Mail - Mail, Sofie (2016)
The purpose of this paper is to investigate the determinants of non-performing loans in commercial banks in Malaysia. This paper focused on 3 bank-specific variables that are believed to have an impact towards the problem loans. 7 local commercial banks have been chosen as samples for this study which covers the year from 2011 until 2015 with total of 35 observations. This paper only focused only on the internal factor of the banks which had caused the rise of non-performing loans . This study also had refers to the previous studies which conducted in other countries or region. This paper only emphasized on Malaysian Commercial banks. At the end of this study, the result would confirm the relationship between non-performing loans ratio (dependent variable) and the bank-specifict factors (return on assets, capital adequacy ratio and bank size).